In silico analysis: Activity of active compounds in passiflora foetida to diabetes - Soendoess, Khadizah; Hernawati, Diana; Putra, Rinaldi Rizal (JPBIO (Jurnal Pendidikan Biologi), 2024)
Plants contain good compounds that are simple to complex including medicinal plants. Herbs are all plant species that are around settlements, cultivated, wild plants that are known to have medicinal properties. An example is the rambusa plant (Passiflora foetida L.). Rambusa leaves are efficacious in relieving fever, insomnia, colds, headaches, diabetes, and asthma. The purpose of this study is to find out physicochemical & pharmacokinetic predictions, toxicity levels, and the affinity of active compounds and a comparison of toxicity levels and affinity of rambusa plants or Passiflora foetida L. with metformin. The method used in this study is qualitative descriptive. Molecular docking with in silicoÂ  approach between active compound Passiflora foetida L. with target protein Alpha-glucosidase subunit B to inhibit blood sugar levels (diabetes). The compound that has the best pharmacokinetic profile compared to metformin is Passifloricin A. 5-Hydroxy-7,4'-dimethoxyflavone, Deidaclin, Linamarin, Volkenin, (1S,4S)-Tetraphyllin B (S)-Tetraphyllin A and Passifloricin A compounds are relatively safer, not mutagen and not toxic to the liver, except Passifloricin A is toxic to the liver, because the compound has a safer level of toxicity compared to the comparison medicine, metformin.